Toxic friendships : knowing the rules and dealing with the friends who break them - Degges-White, Suzanne; Van Tieghem, Judy Pochel, 1960- (Lanham : Rowman & Littlefield, 2015)
Good friends and healthy friendships are crucial to a woman's well-being at every stage of her life. What happens when a friendship turns toxic? When a friend becomes hurtful or mistreats another? When a friend abandons another friend in a time of need? Here, the authors explore such toxic friendships and how women navigate the ups and downs, as well as how broken friendships can be mended, and bad friendships ended. Explaining and illustrating the various rules of friendship at various stages of life, the authors reveal what it takes to be a good friend, how to identify bad friends, and how to move forward when friendships sour.
The need for community -- Friendship patterns from girlhood through older adulthood -- It's a matter of trust -- Just the way you are -- Any friend of hers is a friend of mine -- Being there with emotional support -- A friend in need -- Keep the "friendship favors" balance in check -- Defending your honor -- Bring joy to your friends -- Criticism is not okay -- Jealousy is not okay -- A rule-by-rule guide for parents -- Soccer moms and carpool divas -- Church and civic group friends -- Down the street and on the job : getting along with neighbors and coworkers -- Playing by the rules -- Writing your own rules of relationship -- Taking stock and letting go.
Includes bibliographical references (pages 237-260) and index.
Keywords: Friendship; Female friendship